Clustering and Switching Strategies in Verbal Fluency Tasks: Comparison between Amyotrophic Lateral Sclerosis (ALS) and Healthy Controls - Najme Mardani; Nahid Jalilevand; Mona Ebrahimipour; Mohammad Kamali (Shiraz University of Medical Sciences, 2019)
Background: Recent studies have demonstrated that Amyotrophic Lateral Sclerosis )ALS( patients suffer from cognitive and language impairments. One of the most striking and consistent cognitive dysfunctions in these patients is verbal fluency deficits. The aim of this study is the determination of verbal fluency performance of Persian speakers with ALS. Methods: It was a cross-sectional, analytical-descriptive study. In this study, 30 individuals (15 patients with ALS, and 15 healthy people) were examined by verbal fluency test. Verbal fluency test is a cognitive-linguistic test that has two subtests: phonemic fluency and semantic fluency; in each of them, words normally fall in clusters. Finally, the total number of words, mean cluster sizes and number of switches between clusters are counted and the results are compared between patients with ALS and healthy control groups. Results: There was a significant difference between the patient group and the control group in the mean naming total scores (P≤0.05) and in the mean switching scores (P≤0.05), but not in the mean clusters scores (P≥0.05). Conclusion: Result of this study shows that ALS patients have a deficit in total naming and switching parts of verbal fluency test, but they have no impairment in clustering part. Based on these results, it seems that these patients may have problems in searching in the lexicon, but no problem in accessing words in clusters.